The music of Harry Potter and The Lord of the rings : sounds of home in the fantasy franchise - White, Daniel (Musicologist) (Abingdon, Oxon ; New York : Routledge, 2024)
"The Music of Harry Potter and The Lord of the Rings provides an in-depth study of the music of two of the biggest fantasy franchises, focussing on music's worldbuilding roles within the film-watching experience and elsewhere in videogames, trailers, plays, theme parks and other attractions, and the world of fandom. Daniel White takes a range of approaches and techniques of motivic and thematic musical analysis, and pairs this with transformational harmonic analysis to theorise music's worldbuilding roles in film. Chapters focus in turn on the opening sequences of the case study franchise films, their closing sequences, and on their depiction of houses, homes and homelands. Extra-filmic areas of these fantasy worlds are also explored, including theme parks and other tourist attractions of the Harry Potter franchise, videogames and the immersive power of their music, and the world of fandom with a focus on soundtrack consumption and other musical fan practices. Through this multifaceted approach, readers gain a deeper understanding not only of the music of these franchises, but also of music's power in the multimedia franchise both within and without film to build a home that attracts inhabitants. This book will be valuable for academics and students as well as fans of fantasy franchises"--
The creation of musical worlds : suture in opening sequences -- Homeward bound : desuture in closing sequences and credit songs -- Musical homes and their inhabitation -- Music, wonder and enchantment at tour sites -- Affect, literacy and interaction in game music -- Fan practices/fan products -- Conclusion : home from home.
Keywords: Potter, Harry -- (Fictitious character) -- Songs and music -- History and criticism; Motion picture music -- History and criticism; Amusement park music -- History and criticism; Video game music -- History and criticism; Harry Potter films -- History and criticism; Lord of the Rings films -- History and criticism; PERFORMING ARTS / Film & Video / General; MUSIC / History & Criticism; MUSIC / Genres & Styles / General